Non-intrusive vehicle-based measurement system for drowsiness detection - Ignatius Deradjad Pranowo; Dian Artanto; Muhammad Prayadi Sulistyanto (Universitas Ahmad Dahlan, 2019)
The purpose of this study is for prototyping a non-intrusive vehicle-based measurement system for drowsiness detection. The vehicle-based measurement system aims to achieve the non-intrusive drowsiness detection. The non-intrusive vehicle-based measurement achieved by placing sensors on the steering rod, gas pedal, and brake pedal. Drowsiness can be detected by comparing the position of the steering angle to the desired target angular position, especially when the difference in value of both is greater. Some sensors have been tested to obtain the actual steering angle position. From the test results, sensors that meet the criteria of accuracy are MPU6050 and HMC5883L. Both sensors have been tested in the prototyping of a vehicle-based drowsiness detection system with sufficient results. Furthermore, the prototype of non-intrusive vehicle-based drowsiness detection system has been integrated with interesting driving simulation software. The result has been able to show the actual condition of the steering position, the gas pedal and the brake pedal precisely. Moreover, this prototype opens opportunities to support the study of drowsiness detection using vehicle-based driving simulator.